Control of micro-electro-mechanical systems (MEMS) based micro-mirror devices - Tan, Yan Hao (2015)
The Defense Advanced Research Project Agency (DARPA) mentioned by (Refai, Sluss, & Tull, 2007) had begun the search for an communications alternative in Free Space Optics Micro-Electro-Mechanical Systems (FSO-MEMS). Extending from the communication application, this study seeks to investigate the long range feasibility of the Digital Micro-Mirror Device, DLP3000 DMD to overcome limitations of current Identify Friend or Foe (IFF) systems as current works are focused on short distance applications; encryption; scanning techniques (Lee, 2013; Mirrorcle Technologies Inc., 2014; Schenk et al., 2000; Thakulsukanant, 2013). The presented IFF FSO-MEMS system consist of a Light Source; Detector; Micro-Mirror to generate encrypted messages through optical beam steering in the visible light spectrum. Through the Snell’s Law of Refraction and Beer-Lambert Law, design calculations of DMD Effective Angle of Reflection; DMD Orientation Angle for Back-to-Source Beam Steering; Radiant Power Required suggests that such a system is feasible for a range of 2000m. Experiments at 100m demonstrated the system’s IFF functionality across day and night; static and dynamic platform conditions and observations agree with calculations made. Future work on the system consists of improved Detector stability for image processing; study of system in the Near Infrared (NIR) spectrum for system concealment; integration of system components for increased automation; vertical atmosphere capabilities to extend system’s range of application.